ANALISIS PENGGUNAAN OMOIYARI HYOUGEN DALAM FILM COQUELICOT-ZAKA KARA KARYA SUTRADARA GOROU MIYAZAKI - Dhea Fitri Anggrainy; Meira Anggia Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
Omoiyari hyougen is an expression of caution in speaking and paying attention to the interlocutor. However, there are still many people, especially Japanese language learners in Indonesia who do not really understand the importance of the purpose of omoiyari hyougen when talking with other speakers, especially with Japanese citizens. This study aims to describe the purpose of using omoiyari hyougen in the Coquelicot-Zaka Kara anime. This type of research is qualitative research with descriptive analysis method and data collection using listening technique, followed by free engagement speaking technique and note taking technique. The data of this research is utterances containing omoiyari hyougen and the data source used is the film Coquelicot-Zaka Kara. From the results of the study, it was found that there were 20 data of omoiyari hyougen which were divided into 5 objectives, namely: the goal of maintaining consensus was 1 data, optimizing the comfort of others as much as 6 data, social reciprocity as much as 11 data, intuitive communication as much as 1 data, and feelings of guilt as much as 1 data.